DILEMA DANT ANT ANGAN PEMBELAJARAN E-LEARNING - Hendrastomo, Grendi (MAJALAH ILMIAH PEMBELAJARAN, 2008)
The main focus in this article is the learning model. One model that lately becomes trend is the e-learning. Many strong points from e-learning are able to enhance the essence of learning. Students are pushed to seek for more knowledge, open the door of interaction between lecturers and them widely, without any time nor place limitation. The strong points mentioned above are meant to maximize the process of learning which hopefully will optimize the outcome. Dependency of e-learning with apparatus and technology on the other hand, creates a dilemma and challenge all at once. Three key factors which need to be considered are human resources, supporting infrastructures and implementation. In order to obtain an optimal result of leami11g, these three factors have got to hold up to one and another. In point of fact, these three factors have not actually fuljilled due to 11w11y aspects; for instance, the quality of human resources whose not ye/ been able to master e-learning, minimum infrastructure accessible and how to decide the most suitable learning .rnodel.